Transforming water management in South Africa designing and implementing a new policy framework - Schreiner, Barbara; Hassan, Rashid (Global issues in water policy, 2011)
One of the early set of reforms that South Africa embarked on after emerging from apartheid was in the water sector, following a remarkable, consultative process. The policy and legal reforms were comprehensive and covered almost all aspects of water management including revolutionary changes in defining and allocating rights to water, radical reforms in water management and supply institutions, the introduction of the protection of environmental flows, and major shifts in charging for water use and in the provision of free basic water. Over ten years of implementation of these policy and legislative changes mean that valuable lessons have already been learned and useful experiences gained in the challenge of effective water resources management and water services provision in a middle income country. Transforming Water Management in South Africa analyses and documents these experiences for the benefit of water managers and policy makers in the country, the developing world and the international community at large.